PARTISIPASI MASYARAKAT PADA PELAYANAN KESEHATAN TERSTRUKTUR DAN PARIPURNA - Dharmadi, I Made (PIRAMIDA, 2012)
Government expectation for the health development program is enhancing the communityachievement in independency of their self health care, and one component to show that they areindependent is their ability to pay the cost of their own health. To achieve this, the community stillneeds to be encouraged or even helped by the government to build their awareness and ability toimprove their health behavior as well as pay the expenses of their own health. The most prominentproblem, so far, is people ability to get a better health care since they can not pay especially the cost.Should people need treatment for their health problem, most of them still need to pay through out theirown pocket and hence they realize that the cost is too expensive for them, but they often don’t haveany choice as they can not even go to alternative medicine.Health care shall be consistently maintained since their inability to pay the cost of care when theyare ill has to be limited or avoid. And should they have to face this problem, the system of health careneeds to be restructured or modified to ensure them to be handled well. Particularly in health careexpenditure, the insurance model needs to be introduced and the system based on Indonesian model ofcooperation (“gotong royong”) may be good since it is good to be applied in the developing people inthe basis of more customers to joint and less premium to pay.The government actually has build the system include the payment. In the application however,there still plenty of problems i.e. community participation in separating small part of their money to putit in the community health insurance. The poverty groups have been given a poverty health insurance,the formal group such as government employee, the armies have also been insured by ASKES orJamsostek. The middle low people have to be pushed and subsidized by the government to joint in thecommunity health insurance. It is hardly difficult for them to joint in the health insurance without anyhelp from the government, since their income is too short and their priority for health expenditure isvery low.Beside that, other expenses are also needed to improve the completion of health servicesparticularly to the first step of service in the health centre (Puskesmas). By implementing structured andcompleted services, we wish that the just, well distributed, qualify but affordable services in health willbe easily implemented.
Keywords: Health care system, self health care, insurance.